Taurine Prevents Apoptosis Induced by High Ambient Glucose in Human Tubule Renal Cells. (1st November 2002) - Verzola, Daniela; Bertolotto, Maria Bianca; Villaggio, Barbara; Ottonello, Luciano; Dallegri, Franco; Frumento, Guido; Berruti, Valeria; Gandolfo, Maria Teresa; Garibotto, Giacomo; Deferrari, Giacomo
Abstract : Background: Hyperglycemia selectively triggers apoptosis in tubule and endothelial cells. Taurine, a conditionally essential amino acid, is abundant in several tubule segments, but its role has not been defined fully. It can serve as an osmolyte or as an endogenous antioxidant. Taurine metabolism is altered in diabetes mellitus, with extracellular and intracellular pools reduced. It is still unknown whether taurine can play a role as a protective agent in apoptosis induced by high glucose in tubular cells. Methods: Apoptosis (by annexin V binding and the terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end-labeling method), cellular reactive oxygen species (ROS) formation (by fluorescent probe 2′-7′ dichlorofluorescin diacetate and FACScan flow cytometry), and Bcl-2 and Bax proteins (by immunostaining) were studied in a human proximal tubular cell line (HK-2) grown in a medium with physiologic (5.5 mM) or high (30 mM) glucose concentrations for 48 hours. In separate experiments, taurine (3-24 mM) was added to the media. Results: The exposure of human tubule cells to 30 mM glucose for 48 hours resulted in a significant increase in apoptosis compared with 5.5 mM glucose (35±8% vs. 6±3%, p<0.001). Thirty mM mannitol failed to induce the effects of high glucose. High glucose-mediated apoptosis was associated with a decrease in the expression of Bcl-2 (-87%) and a twofold increase in the expression of Bax protein. Taurine had a dose-dependent effect in preventing high-glucose-induced apoptosis (-78%, p<0.001 at 24 mM). Moreover, with taurine, intracellular ROS decreased by 34% (p<0.05), and changes in intracellular ROS formation induced by taurine at 24 hours predicted the variations in the apoptotic index at 48 hours (r=0.87, p<0.02). Other antioxidants, such as glutathione and N -acetylcysteine, also attenuated the high glucose-induced apoptosis. Conclusion: These results demonstrate that taurine attenuates hyperglycemia-induced apoptosis in human tubular cells via an inhibition of oxidative stress. Taurine might act as an endogenous antioxidant in tubule cells and could exert a beneficial effect in preventing tubulointerstitial injury in diabetic nephropathy.